Revision of Palaearctic and Oriental Necrophila Kirby & Spence, part 2: subgenus Chrysosilpha Portevin (Coleoptera: Silphidae) - Růžička, Jan; Schneider, Jan; Qubaiová, Jarin; Nishikawa, Masaaki (Zootaxa, 2012)
A taxonomic revision of the subgenus Chrysosilpha Portevin, 1921 (of the genus Necrophila Kirby & Spence, 1828) ispresented. Three valid species are recognized: (1) N. (C.) formosa (Laporte, 1832), comb. nov. (ex Silpha Linnaeus, 1758),widely distributed from Laos and Vietnam through the Malay Peninsula, to Sumatra and Bali, with Silpha chloropteraLaporte, 1840 and Chrysosilpha chloroptera var. magnifica Portevin, 1921 as newly established junior subjectivesynonyms; (2) N. (C.) renatae (Portevin, 1920), comb. nov. (ex Silpha), endemic to Sulawesi; and (3) N. (C.) viridis(Motschulsky, 1861), comb. nov. (ex Oiceoptoma Leach, 1815), endemic to the Philippines. Lectotypes are designated forSilpha formosa Laporte, 1832; Silpha chloroptera Laporte, 1840 and Chrysosilpha chloroptera var. magnifica Portevin,1921. Georeferenced records for all three species are mapped. Parsimony analysis supports the monophyly ofChrysosilpha, with N. (C.) formosa as the sister to a clade of N. (C.) renatae and N. (C.) viridis. Geometricalmorphometrics (thin-plate spline) discriminated the three species of Chrysosilpha; the first two relative warp axesindicated 70.31% shape variation in males and 77.18% in females, which was further confirmed by MANOVA to be highlysignificant. Canonical variate analysis indicated no overlap between the three taxa and enabled a 100% correct classification of each specimen to its group mean.